Time-dependent changes of plasma adiponectin concentration in relation to coronary microcirculatory function in patients with acute myocardial infarction treated by primary percutaneous coronary intervention. Issue 3 (March 2015) - Trifunovic, Danijela; Stankovic, Sanja; Marinkovic, Jelena; Beleslin, Branko; Banovic, Marko; Djukanovic, Nina; Orlic, Dejan; Tesic, Milorad; Vujisic-Tesic, Bosiljka; Petrovic, Milan; Nedeljkovic, Ivana; Stepanovic, Jelena; et al.
Abstract: Background and purpose: To analyze plasma adiponectin kinetics in patients with ST-segment elevation myocardial infarction (STEMI) treated by primary percutaneous coronary intervention (pPCI) and its association with coronary flow reserve (CFR), an index of coronary microcirculatory function. Methods: A total of 96 consecutive patients with the first anterior STEMI treated by pPCI without heart failure were included. CFR was assessed on the 7th day after pPCI. Plasma adiponectin was measured on admission before pPCI, and on the 2nd and 7th day after pPCI. Results: Adiponectin concentration was the highest on admission, declined to the lowest level on the 2nd day, and rose on the 7th day remaining below admission values. Impaired coronary microcirculatory function (CFR < 2) was observed in 41% of the patients. Adiponectin concentrations significantly positively correlated with CFR, and the strongest correlation was with the 2nd day adiponectin ( r = 0.489, p < 0.001). In multivariate models, adiponectin concentrations were independent predictors of impaired CFR [on admission: odds ratio (OR) 0.175, confidence interval (CI): 0.047–0.654, p = 0.010; 2nd day: OR 0.146, 95% CI: 0.044–0.485, p = 0.002; 7th day: OR 0.198, CI: 0.064–0.611, p = 0.005]. The best power to predict impaired CFR was the 2nd day adiponectin. Delta values of adiponectin (differences between adiponectin concentrations) did not correlate with CFR. Conclusions: In patients with the first anterior STEMI treated by pPCI plasma adiponectin concentrations before and after pPCI are strongly associated with CFR. Our results support the hypothesis that low adiponectin, especially during the early post-pPCI period, carries the risk for impaired coronary microcirculatory function in STEMI patients.